The Symbolic Consumption in the Tween’s Lifestyle Formation (2019)
The world is currently facing more than ever new consumption forms loaded with symbolic contents to show certain appearance or to judge others; the sense of property is shown as a primary indicator of who you are and how you relate to others. This article pretends, first, to glimpse the goods and trademarks acquisition or possession as an expression of individuals; and second, to understand the role that symbolic consumption plays in the tween’s lifestyle. The author’s intention is to show the need to generate some understanding of social consumption phenomena taking tween’s consumers as subjects of study.